Immunization in Periodontics: A Systematic Review - Reddy, N Raghavendra; -, Yuvraja; Nalini, Esther; Devi, Renuka; -, Arun (Journal of Orofacial Research, 2013)
Background: Formulation of a vaccine against pathogenic microorganisms causing periodontal diseases has been under research for a decade. Many in vitro and in vivo studies have been made in this regard. The aim of this study is to review all preclinical (i.e. animal) and in vivo studies that presents supporting evidence for the feasibility of formulating a prophylactic human periodontal vaccine. Materials and methods: A manual and electronic literature search was made for animal studies up to 2011 that presented clinical, morphologic (alveolar bone level), and immunologic data for the efficacy of a prophylactic periodontal vaccine. A total of 31 studies are included out of which nine are in vivo studies. Results: In vitro studies revealed a definitive inhibitory effect of vaccines over periodontal disease causing organisms and their vulnerability toward such agents. Among the studies reviewed, in vitro outnumbered the in vivo studies and there is definitely a lack in quality and quantity of human trials in this regard. Most in vitro studies have shown results in favor of vaccines preventing the periodontal diseases by action against pathogenic organisms. Conclusion: Because of the insufficient quality and quantity of human trials, no adequate evidence could be gathered to use the beneficial effects of these animal experiments to formulate a prophylactic human periodontal vaccine. Thus, good quality animal and human trials are needed in this field of vaccination against periodontal diseases.